Impact of Product Quality, Price, and Promotion on Purchase Decision of Dinda Fashion Products in Denpasar - I Wayan Gede Antok Setiawan Jodi; Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra; I Made Surya Prayoga; Made Santana Putra Adiyadny (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine impact of product quality, price, and promotion on purchase decision of Dinda Fashion Products in Denpasar. The sample in this study used 80 people who were the respondents of Dinda Fashion consumers in Denpasar City. The data analysis technique used in this research is multiple regression analysis. The results showed that: (a)there was a significant and positive effect between product quality and purchase decision with a coefficient value of 4.484 and a significance value of 0.000, (b)there was a significant and positive effect between price and purchase decision with a coefficient value of 3.958 and a significance value of 0.001, and (c)there was a significant and positive effect between promotion and purchase decision with a coefficient value of 4.721 and a significance value of 0.000.